98.7k views
5 votes
How do I solve explain steps

How do I solve explain steps-example-1

1 Answer

6 votes

Answer:

There's no real solutions to this expression.

Explanation:

5x - (3 - 2x) = - (-x - 7) + 6x

  • First we need to get rid of the parenthesis and to do that we multiply inside the parenthesis with -1

5x - 3 + 2x = x + 6 + 6x (remember, negative × negative = positive)

  • Now add/subtract like terms:

5x + 2x - 3 = 7x - 3

x + 6x + 7 = 7x + 7

  • Rewrite the equation:

7x - 3 = 7x + 7, 7x will eliminate each other so we will be left with,

-3 = 7 which cannot be true so we say there's no real solutions to this expression.

User BrendanMcKee
by
5.3k points